Is the Cycle the Trend? : Evidence From the Views of International Forecasters - Bluedorn, John.; Leigh, Daniel (Washington, D.C. : International Monetary Fund, 2018)
We revisit the conventional view that output fluctuates around a stable trend by analyzing professional long-term forecasts for 38 advanced and emerging market economies. If transitory deviations around a trend dominate output fluctuations, then forecasters should not change their long-term output level forecasts following an unexpected change in current period output. By contrast, an analysis of Consensus Economics forecasts since 1989 suggest that output forecasts are super-persistent-an unexpected 1 percent upward revision in current period output typically translates into a revision of ten year-ahead forecasted output by about 2 percent in both advanced and emerging markets. Drawing upon evidence from the behavior of forecast errors, the persistence of actual output is typically weaker than forecasters expect, but still consistent with output shocks normally having large and permanent level effects.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet